Assessing farmer perceptions on livestock intensification and associated trade-offs using fuzzy cognitive maps; a study in mixed farming systems in the mid-hills of Nepal - Alomia-Hinojosa, Victoria (2023)
Intensified livestock production is considered as a promising pathway for smallholder farmers. Nevertheless, this pathway may entail prohibitive investment requirements of labour, capital or trade-offs at farm level that preclude sustainable intensification. We used fuzzy cognitive mapping (FCM) to assess farmers' perceptions of changes in the farm household system resulting from adding livestock to their mixed farms. Farmers identified trade-offs between the increased income and farmyard manure production versus increases in labour requirements for fodder imports. Furthermore, a sensitivity analysis performed on the FCMs showed that an increase in milk market demand could have strong positive effects on livestock production and income. We conclude that FCM is a good tool to rapidly identify trade-offs and analyse perceptions of farmers which revealed that although they consider intensification a promising strategy, the perceived deepening of labour constraints and increasing dependency on fodder import makes a concurrent (sustainable) intensification of these farm systems unlikely.